Pengaruh Leverage Dan Arus Kas Terhadap Kinerja Keuangan - M Alfiandri Setiawan; Andri Indrawan; Venita Sofiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the effect of leverage and cash flow on financial performance. The research method used in this research is using quantitative methods with descriptive and associative approaches. The population and sample in this study are the financial statements of 23 trading companies in the manufacturing sector listed on the Indonesia Stock Exchange for the 2015-2020 period. This research technique uses classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test. The collection technique used documentation and interview methods. The results showed that leverage had no partial effect on ROA and cash flow had no partial effect on ROA. Simultaneously, leverage and cash flow affect profitability. Keywords : Leverage, Cash Flow, Financial Performance